2015
DOI: 10.1021/acs.joc.5b01489
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Naphthalenediyl-Bridged Molecular Gyrotops: Rotation of the Rotor and Fluorescence in Solution

Abstract: Macrocage molecules with a bridged π-electron system have been reported as molecular gyrotops in which the π-electron system can rotate within the cage. We recently reported the dynamics of the rotor in solution using 1,4-naphthalenediyl-bridged molecular gyrotops, which consist of cages formed of three C14, C16, or C18 chains. In this work, we synthesized novel gyrotops with C15 and C17 chains and systematically investigated the activation energies for the rotation of the rotor in solution. The activation ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 64 publications
3
27
0
Order By: Relevance
“…For instance, 18 hasb een probed by 13 C-13 CE XSY by Setaka and colleagues, who found that the dynamics of the naphthalene rotor (108-10 À5 s À1 )a ppears to be much slower than the respective fluorescencetimescale. [52] In certain cases, the rotation of relatively small trigonal rotors such as tBu groups can be slowed down. Kurskii and coworkers [53] observed clearly sluggish tBu rotationi nd imeric species derived from 2,5-di-tert-butylcyclopentadienone.…”
Section: Trigonal Rotorsmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, 18 hasb een probed by 13 C-13 CE XSY by Setaka and colleagues, who found that the dynamics of the naphthalene rotor (108-10 À5 s À1 )a ppears to be much slower than the respective fluorescencetimescale. [52] In certain cases, the rotation of relatively small trigonal rotors such as tBu groups can be slowed down. Kurskii and coworkers [53] observed clearly sluggish tBu rotationi nd imeric species derived from 2,5-di-tert-butylcyclopentadienone.…”
Section: Trigonal Rotorsmentioning
confidence: 98%
“…Rotation of a molecular fragment inside another fragment, termed “gyrotop” (Scheme ) is very closely related to trigonal rotors. For instance, 18 has been probed by 13 C‐ 13 C EXSY by Setaka and colleagues, who found that the dynamics of the naphthalene rotor (10°–10 −5 s −1 ) appears to be much slower than the respective fluorescence timescale …”
Section: Intramolecular Rotationmentioning
confidence: 99%
“…Such species carry primed numbers throughout this manuscript. Setaka has realized similar chemistry when the P–M–P linkages are replaced by Si–arylene–Si linkages (e.g., arylene = p -C 6 H 4 ). , …”
Section: Introductionmentioning
confidence: 99%
“…One can make these molecules uni‐directional simply by adding dipole moment in the rotor unit [1c] . The Garcia‐Garibay [1b–f] and Setaka [1g–l] groups have independently synthesized molecular rotors having organic rotor unit and explored their rotational properties. The group of Gladysz has extensively contributed towards design and synthesis of various molecular gyroscopes having an inorganic rotor unit in the molecule and understanding their rotational behavior [1a,5] .…”
Section: Introductionmentioning
confidence: 99%